P332 A treat-to target strategy guided by pan-enteric valuation in paediatric Crohn's disease improves outcomes at 2 years. (16th January 2018) - Oliva, S; Cohen, S; Aloi, M; Mallardo, S; Viola, F; D'Arcangelo, G; Maccioni, F; Hassan, C; Papoff, P; Cucchiara, S
Abstract: Background: Sparse data exist on the long-term outcomes of mucosal healing (MH) in children with Crohn's disease (CD). It is uncertain if a treat-to-target approach might be a clinically and cost-effective strategy improving deep remission (DR) rate and outcomes. Previously, we reported MH and DR rates on the entire GI tract by performing three pan-enteric capsule evaluations and applying a treat-to-target strategy over 52 weeks in children with CD. This study evaluates the impact of this approach at 104 weeks. Methods: Children with known CD were prospectively recruited and underwent PCE at 0, 24, 52 and 104 weeks. Therapy was calibrated according to pan-enteric capsule endoscopy (PCE) and magnetic resonance enterography (MRE) results in a treat-to-target approach. Results at week 52 and 104 were compared, and long-term outcomes between patients with or without complete MH were calculated using an intention-to-treat (ITT) analysis of clinical relapse, need for steroids and/or treatment escalation, hospitalisation and surgery. Results: Forty-eight patients were recruited at baseline and underwent a treat-to-target approach for one year. The 52-week assessment demonstrated a 58% DR rate compared with 21% of baseline ( p < 0.05). In all, 42 underwent the 104-week PCE evaluation (2 developed an ileo-cecal valve stricture at 52 weeks; 4 were lost to follow-up). MH was present in 10 at baseline; 28 at 52 weeks. There was only 7% drop-off in MH compared with 1-year assessment. In ITT analysis, complete MH at 52 weeks was associated with decreased clinical relapse rate ( p < 0.003), reduced steroid usage ( p < 0.0005), fewer treatment escalation ( p < 0.0003), and diminished hospitalisation rates ( p < 0.0001). There was a decreased need for surgery, but not statistically significant ( p = 0.065). The overall diagnostic yield of PCE, MRE and biomarkers were 54%, 37% and 33%, respectively ( p < 0.05). Conclusions: Treat-to-target approach can significantly increase DR rates on the entire GI tract by using PCE and it seems to be cost-effective. When MH is achieved by this strategy, it is sustainable (93%) over a one-year period and correlates with improved patient outcomes, including decreased need for steroids, treatment escalation, hospitalisation and surgery.